EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK TEKNIK ROLE PLAYING UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA KELAS XI DI SMA NEGERI 8 KOTA JAMBI - Riyanto, Dedi; Yulianto, Y; Yanto, Y (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2024)
This research aims to increase the self-confidence of students in class XI of SMA Negeri 8 Jambi City. The approach to this research uses an experimental approach with a correlation method. The sampling technique used purposive sampling with a sample size of 10 people and 8 students who had low self-confidence were taken. Based on the research results, a significance value of 0.000 kecil dari 0.05 was obtained and the calculated t value was kecil t table or -0.675 kecil dari 0.2172. So Ho was rejected, which means there was an increase in students' self-confidence after undergoing treatment 3 times through the role playing technique group guidance service.